Enfoques teóricos e metodológicos das ações de extensão rural do IRGA - Saragoso, Tábata Morena Rodrigues (2023)
Rural extension was institutionalized in Brazil from 1950 onwards with the aim of integrating peasants into the market economy through the modernization of agriculture through the transfer of technologies. It was during this period that technical assistance took on an extension character, marking the so-called Technical Assistance and Rural Extension (ATER). Extension services have already been analyzed from different perspectives; in the research in question, the following categorization was adopted: welfare humanism, corresponding to services that targeted the poorest farmers and prioritized activities related to family well-being; productivist diffusionism, when the Brazilian State subsidized technological modernization in the agricultural sector through the Green Revolution principles; rethinking rural extension, a period of intense criticism of the diffusionist methods used in extension; institutional pluralism, which represented heterogeneity in the supply and execution of rural extension services. The Rio Grandense do Arroz Institute (IRGA) was institutionalized in 1940 as a public agency and linked to the Secretariat of Agriculture of Rio Grande do Sul, and its objective is to promote the sustainable development of the rice farming sector through the generation and dissemination of knowledge and technologies. IRGA plays a fundamental role in supporting rice production, and through the Rice Experimental Station (EEA) it promotes research and disseminates technological innovations in production management to farmers. Furthermore, the IRGA was founded as a class entity, which is why it defends the economic and political interests of rice farmers. For 76 years, IRGA has periodically published the magazine Lavoura Arrozeira, its main information vehicle, considered a reference in the dissemination of agricultural technologies. Currently the magazine has 473 editions, of which 147 make up the collection of the 6th Technical Assistance and Extension Center (NATE) in Santa Maria/RS. Given this, the research aimed to identify the theoretical and methodological approaches to IRGA's rural extension actions based on an exploratory and quantitative-qualitative content analysis of the information conveyed to the editions of the magazine Lavoura Arrozeira. We sought to understand the historical trajectory of rural extension services in Brazil, investigate the origin of rice production in the state and the context of creation of IRGA, analyze the main methodologies adopted in extension actions and how they change in the face of different projects politicians. As results, it was observed that the main ATER action developed by IRGA is the field day in the EEA guided by diffusionist and productivist principles, the transfer of technologies is much more evident than the educational approach, and agricultural policies may or may not influence the theoretical and methodological guidelines of IRGA's rural extension actions.